Aerial Rotation Effects on Vertical Jump Performance Among Highly Skilled Collegiate Soccer Players. Issue 4 (April 2017) - Barker, Leland A.; Harry, John R.; Dufek, Janet S.; Mercer, John A.
Abstract : Abstract: Barker, LA, Harry, JR, Dufek, JS, and Mercer, JA. Aerial rotation effects on vertical jump performance among highly skilled collegiate soccer players. J Strength Cond Res 31(4): 932–938, 2017—In soccer matches, jumps involving rotations occur when attempting to head the ball for a shot or pass from set pieces, such as corner kicks, goal kicks, and lob passes. However, the 3-dimensional ground reaction forces used to perform rotational jumping tasks are currently unknown. Therefore, the purpose of this study was to compare bilateral, 3-dimensional, and ground reaction forces of a standard countermovement jump (CMJ0 ) with those of a countermovement jump with a 180° rotation (CMJ180 ) among Division-1 soccer players. Twenty-four participants from the soccer team of the University of Nevada performed 3 trials of CMJ0 and CMJ180 . Dependent variables included jump height, downward and upward phase times, vertical (Fz) peak force and net impulse relative to mass, and medial-lateral and anterior-posterior force couple values. Statistical significance was set a priori at α = 0.05. CMJ180 reduced jump height, increased the anterior-posterior force couple in the downward and upward phases, and increased upward peak Fz ( p ⩽ 0.05). All other variables were not significantly different between groups ( p > 0.05). However, we did recognize that downward peak Fz trended lower in the CMJ0 condition ( p = 0.059), and upward net impulse trended higher in the CMJ0 condition ( p = 0.071). It was concluded that jump height was reduced during the rotational jumping task, and rotation occurred primarily via AP ground reaction forces through the entire countermovement jump. Coaches and athletes may consider additional rotational jumping in their training programs to mediate performance decrements during rotational jump tasks.